The Effect of Different Organic Acids and Their Combination on the Cell Barrier and Biofilm of Escherichia coli - Qing-Yang Ji; Wenqiong Wang; Haodong Yan; Hengxian Qu; Yang Liu; Yi Qian; Ruixia Gu (Foods, 2023)
Organic acids are natural antimicrobial compounds commonly used in the food industry. In this study, acetic, lactic, butyric, citric, and malic acid at minimum inhibitory concentrations and their combinations at optimal inhibition concentrations were used to treat E. coli, and the effects on the cell barrier and biofilm of E. coli were evaluated. Acetic acid showed the highest membrane-damaging effect, while citric acid and malic acid could specifically damage the cell wall of E. coli, leading to alkaline phosphatase leakage. The RT-qPCR results showed that organic acids upregulated the membrane-protein-related genes of E. coli, and the combination of organic acids had a wider range of effects than single organic acid treatment. Moreover, organic acids inhibited the formation of E. coli biofilm and cellular activity within the biofilm. This study showed that the combination of organic acids plays a synergistic inhibitory role mainly through multiple destructive effects on the cell barrier and exhibited synergistic anti-biofilm effects. The three–three combination of acetic, lactic acid, and a third organic acid (butyric, citric, or malic) can play a better synergistic antibacterial effect than the two-pair combination of acetic and lactic acid. These findings have implications for the usage, development, and optimization of organic acid combinations.